The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1016/j.marenvres.2008.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Water column organic carbon in a Pacific marginal sea (Strait of Georgia, Canada)

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…PON and biogenic Si detritus are estimated to be 0.2 of the microphytoplankton biomass and DON is 0.1 of PON. Semilabile DON is generally higher than PON in the SoG [ Johannessen et al ., ], however, model DON is not sensitive to the initialization value and exceeds model PON after 30 days. Since model pH and Ω A are not sensitive to initial carbon conditions after 30 days, IOS carbon profiles from the 11 September 2011 cast date are used to initialize DIC and TA.…”
Section: Methodsmentioning
confidence: 99%
“…PON and biogenic Si detritus are estimated to be 0.2 of the microphytoplankton biomass and DON is 0.1 of PON. Semilabile DON is generally higher than PON in the SoG [ Johannessen et al ., ], however, model DON is not sensitive to the initialization value and exceeds model PON after 30 days. Since model pH and Ω A are not sensitive to initial carbon conditions after 30 days, IOS carbon profiles from the 11 September 2011 cast date are used to initialize DIC and TA.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, although the tryptophan-like component C6, represents a minor proportion of total fluorescence, even a small proteinaceous fraction of the overall DOM pool can play a major role in overall bioavailability and bacterial utilization of DOM (Berggren et al, 2010;Guillamette and Giorgio, 2011). These contributions of stream-exported DOM may represent a relatively fresh, seasonally consistent contribution of terrestrial subsidy from streams to the coastal ecosystem, which in this region is relatively lower in carbon and nutrients throughout much of the year (Whitney et al, 2005;Johannessen et al, 2008).…”
Section: Doc Export From Small Catchments To the Coastal Oceanmentioning
confidence: 99%
“…Hofmann et al (2009) found that adding a biogeochemical model to a prescribed physical mixing scenario in the highly polluted Scheldt estuary decreased the low-salinity pH minimum due to strong remineralization of abundant anthropogenic organic carbon (Frankignoulle et al, 1996) and increased pH at higher salinity due to intense outgassing (Schiettecatte et al, 2006). In contrast the Fraser River estuary is biologically productive and 20 deep (model site is deeper than 300 m) and much of the organic matter produced locally sinks and is remineralized well below the surface layer (Johannessen et al, 2008) resulting in increased estuarine pH across the salinity range during summer (Ianson et al, 2016) compared with the two-endmember mixing model. Still, this simplified case reproduces the overall estuarine pH sensitivity that we observe in the coupled model.…”
Section: Two-endmember Conservative Mixingmentioning
confidence: 99%